Effect of Gastrointestinal Radiation Injury Symptoms and Risk Factors in Al-Najaf Province - Mohammed , Hassanein Fadel; Al-Najem , Hadeel Thaer Ahmed (Medical Science Journal for Advance Research, 2025)
Background: Gastrointestinal radiation injury is one of the most common and distressing complications resulting from exposure to ionizing radiation, particularly during radiotherapy for pelvic or abdominal malignancies. The gastrointestinal tract is highly sensitive to radiation, which may lead to acute or chronic symptoms that affect the patient’s quality of life. Despite advancements in radiation techniques, these injuries remain a clinical concern, especially in regions with limited access to advanced protective methods. Objectives: To identify the most common symptoms and key risk factors associated with gastrointestinal radiation injury among patients in Al-Najaf Province, Iraq. Results: Data analysis revealed that the most prevalent symptoms were abdominal pain (76%), diarrhea (68%), nausea and vomiting (61%), bloating (55%), and weight loss or anorexia (48%). Risk factors included high cumulative radiation dose, repeated imaging procedures involving the abdominal region, lack of proper shielding, pre-existing gastrointestinal conditions, smoking, and poor nutritional status. Patients who received pelvic radiotherapy showed higher symptom severity. Conclusion: Gastrointestinal radiation injury is a significant and under-recognized health issue among radiology patients in Al-Najaf Province. Several risk factors—both medical and lifestyle-related—contribute to the development and severity of symptoms, particularly in patients undergoing frequent or high-dose radiation exposure.